Long-term nutrition education reduces several risk factors for type 2 diabetes mellitus in Brazilians with impaired glucose tolerance - Pimentel, Gustavo D.; Mclellan, Katia Cristina Portero [UNESP]; Oliveira, Erick P. [UNESP]; Spada, Ana P. M. [UNESP]; Oshiiwa, Marie; Zemdegs, Juliane C. S.; Barbalho, Sandra M. (Pergamon-Elsevier B.V. Ltd, 2010)
The aim of this study was to evaluate the effects of a nutrition education program (NEP) on anthropometric, dietetic, and metabolic parameters in high-risk subjects for type 2 diabetes mellitus. Fifty-one participants, both sexes, were randomly assigned to either the control (58.8%) or the intervention (NEP) group. The intervention group received frequent individual and group nutritional counseling from a team of nutritionists. Participants were assessed at baseline (M0) and after 12 months (M1) for anthropometric, dietetic, and metabolic parameters. The hypothesis was that high-risk subjects for type 2 diabetes mellitus participating in NEP would show an improvement in these parameters. At M1, the intervention group showed a significant decline in body weight (-3.4%), body mass index (-5.7%), cholesterol intake (-49.5%), fasting glycemia (-14.0%), fasting insulin (-9.0%), postprandial glycemia (-21.0%), postprandial insulin (-71.0%), total serum cholesterol (-23.0%), and glycated hemoglobin (-24.0%). A decrease in energy intake (5%, P = .06) and low-density lipoprotein cholesterol (25%, P = .07) was observed in the interventional group, although it did not reach statistical significance. In contrast, the control group presented a significantly higher energy intake (19%, P = .04) and a nonsignificant increase in consumption of all macronutrients. The long-term NEP was found to improve anthropometric, dietary, and metabolic parameters in high-risk subjects for type 2 diabetes mellitus. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Nutritional education; Prevention; Type 2 diabetes mellitus; Metabolic syndrome; Human